The Longevity Properties of 1,2,3,4,6-Penta-O-Galloyl-β-D-Glucose from Curcuma longa in Caenorhabditis elegans - Ahn, Dalrae; Cha, Dong Seok; Lee, Eun Byeol; Kim, Ban Ji; Lee, So Yeon; Jeon, Hoon; Ahn, Min-Sil; Lim, Hye Won; Lee, Heon Yong; Kim, Dae Keun (Biomolecules & therapeutics, 2013)
Here in this study, we isolated 1,2,3,4,6-penta-O-galloyl-β-D-glucose (PGG) from Curcuma longa L. and elucidated the lifespanextending effect of PGG using Caenorhabditis elegans model system. In the present study, PGG demonstrated potent lifespan extension of worms under normal culture condition. Then, we determined the protective effects of PGG on the stress conditions such as thermal and oxidative stress. In the case of heat stress, PGG-treated worms exhibited enhanced survival rate, compared to control worms. In addition, PGG-fed worms lived longer than control worms under oxidative stress induced by paraquat. To verify the possible mechanism of PGG-mediated increased lifespan and stress resistance of worms, we investigated whether PGG might alter superoxide dismutase (SOD) activities and intracellular ROS levels. Our results showed that PGG was able to elevate SOD activities of worms and reduce intracellular ROS accumulation in a dose-dependent manner.